Thermal ecology and physiology of an elongate and semi-fossorial arthropod, the bark centipede. (December 2020) - Cox, Christian L.; Tribble, Hilariann O.; Richardson, Shane; Chung, Albert K.; Curlis, John David; Logan, Michael L.
Abstract: Organismal performance is strongly linked to temperature because of the fundamental thermal dependence of chemical reaction rates. However, the relationship between the environment and body temperature can be altered by morphology and ecology. In particular, body size and body shape can impact thermal inertia, as high surface area to volume ratios will possess low thermal mass. Habitat type can also influence thermal physiology by altering the opportunity for thermoregulation. We studied the thermal ecology and physiology of an elongate invertebrate, the bark centipede ( Scolopocryptops sexspinosus ). We characterized field body temperature and environmental temperature distributions, measured thermal tolerance limits, and constructed thermal performance curves for a population in southern Georgia. We found evidence that bark centipedes behaviorally thermoregulate, despite living in sheltered microhabitats, and that performance was maintained over a broad range of temperatures (over 20 °C). However, both the thermal optimum for performance and upper thermal tolerance were much higher than mean body temperature in the field. Together, these results suggest that centipedes can thermoregulate and maintain performance over a broad range of temperatures but are sensitive to extreme temperatures. More broadly, our results suggest that wide performance breadth could be an adaptation to thermal heterogeneity in space and time for a species with low thermal inertia. Highlights: This is one of the first studies of the thermal ecology of scolopendramorph centipedes. Centipedes behaviorally thermoregulate in thermally buffered microhabitats. The thermal performance curve of centipedes matches Tb and VTmax . Centipedes maintain high performance over a wide range of temperatures. Centipede thermal biology is adapted to rapid equilibration and habitat variability.